Advertising of tobacco products at point of sale: who are more exposed in Brazil? - Adriana Bacelar Ferreira-Gomes; Lenildo de Moura; Silvânia Suely de Araujo-Andrade; Felipe Lacerda-Mendes; Cristina A Perez; Zohra Abaakouk (Instituto Nacional de Salud Pública, 2017)
Objective. To describe the adult population perception of cigarette advertising at point of sale, according their tobaccouse status and socio-demographic characteristics such as sex, age, race/color, region, household location and schooling. Materials and methods. A multivariable analysis was carried out using data from the Global Adult Tobacco Survey in 2008 and the National Health Survey in 2013. Results. Both surveys showed that among nonsmokers: women, young adults and those who had over 10 years of schooling had more frequently noticed advertising of cigarettes at point of sale. It was also observed that among the population with fewer years of schooling these proportions increased significantly. Conclusion. A measure that completely bans tobacco advertising would be more effective to protect the vulnerable groups from tobacco consumption.